Gender difference in allergic airway remodelling and immunoglobulin production in mouse model of asthma. Issue 5 (21st June 2013) - Takeda, Masahide; Tanabe, Masako; Ito, Wataru; Ueki, Shigeharu; Konnno, Yasunori; Chihara, Mami; Itoga, Masamichi; Kobayashi, Yoshiki; Moritoki, Yuki; Kayaba, Hiroyuki; Chihara, Junichi
Abstract Background and objective Epidemiological studies have shown that the prevalence of adult asthma and severe asthma is higher in women. It has also been reported that female mice are more susceptible than males to the development of allergic airway inflammation and airway hyperresponsiveness (AHR). The influence of gender difference in the pathogenesis of severe asthma, especially airway remodelling in an animal model, has been studied rarely. We investigated gender difference in the development of airway remodelling using a long‐term antigen‐challenged mouse asthma model. Methods Following ovalbumin (OVA)/alum intraperitoneal injection, male or female mice (BALB/c) were challenged with aerosolized 1% OVA on 3 days/week for 5 weeks, and differences in AHR, airway inflammation and airway remodelling between the sexes were investigated. Results In OVA‐sensitized and OVA‐challenged (OVA/OVA) female mice, eosinophils, lymphocytes, T‐helper type 2 cytokines and growth factors in bronchoalveolar lavage fluid were increased compared with OVA/OVA male mice. Histological features of airway remodelling were also increased in OVA/OVA female mice. Serum total and OVA‐specific immunoglobulin E (IgE) and serum IgA were significantly elevated in OVA/OVA female mice. Conclusions These results indicate that female mice experience more airway remodelling compared with male mice. These results suggest the involvement of sex hormones and gender differences in cellular functions in airway remodelling.